The Atlantic Constellation Project as Hispanic-Portuguese promoter within the Multipolar International System: Aportes tecnológicos a la Unión Europea (UE) y a la Organización del Tratado del Atlántico Norte (OTAN) - Barragán Fernández, Bruno Israel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Hispanic-Portuguese Treatment of Friendship and Cooperation implements the economic reactivation of both countries and the European Next Generation EU Funds boosts their technological initiatives allowing the implementation of a project that will establish a 16-Satellite Space Network which will provide a wide and valuable information in order to prevent situations of emergencies, improve the quality of life and the adaptation of ecological transition, generation of high quality employment, promote business growth with both public and private funds and simultaneously obtaining required data and reports by the EU / OTAN intelligence agencies.